2019
DOI: 10.5398/tasj.2019.42.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phloroglucinol on In Vitro Methanogenesis, Rumen Fermentation, and Microbial Population Density

Abstract: This study investigated the effect of phloroglucinol (1,3,5-trihydroxybenzene) supplementation alone on methane production, rumen fermentation profiles, and microbial population structure of mixed in vitro cultures. Treatments included a control group containing a substrate with no supplement, and substrates supplemented with 2, 4, 6, 8, or 10 mmol/L of phloroglucinol. The results revealed that phloroglucinol was able to decrease methane production in a dose-dependent manner. The highest decrease was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Gas production calculations using equations from López et al . [ 18 ] identified reductions in maximum gas production (B), but gas production rates (k) and time lags (L) were significantly increased (p < 0.05) by HMT. Methane concentrations were affected during initial 12 h incubations (p < 0.01), but gas production at 24 h–48 h showed no significant effects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gas production calculations using equations from López et al . [ 18 ] identified reductions in maximum gas production (B), but gas production rates (k) and time lags (L) were significantly increased (p < 0.05) by HMT. Methane concentrations were affected during initial 12 h incubations (p < 0.01), but gas production at 24 h–48 h showed no significant effects.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was related to methanogen populations, which were not significantly affected by HMT treatment and increased acetate production. The CH 4 production in the rumen can be affected directly by methanogen population or indirectly by nutrient digestion [ 18 ]. In this study, HMT increase acetate concentration in the rumen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chitosan from CHIJC02 exhibited both direct and indirect effects on methanogenesis inhibition, as evidenced in the decrease of methanogen population and the limitation of substrate availability and changes in microbial community composition resulting in reduced CH 4 production [ 49 ]. It was observed that chitosan can reduce the methanogen population in the CHIJC02 treatment.…”
Section: Discussionmentioning
confidence: 99%